Evidence-based policymaking : envisioning a new era of theory, research, and practice - Bogenschneider, Karen; Corbett, Tom, 1944- (Abingdon ; New York, NY : Routledge, 2021)
"The traditional story of how we do social policy in this country reveals a disconnect between the research community, that is producing hundreds of studies relevant to public policy, and the policy community, that is making hundreds of decisions that would benefit from research evidence. This second edition tells an even stronger, more substantiated story of all it will take to connect researchers and policymakers: A fresh look into what policymakers and the policy process are like, as told by policymakers themselves and the researchers who study and work with them An elaboration of Community Dissonance Theory, which points to culture as the culprit for why conflicts and miscommunication occur between researchers and policymakers New insights on the purposes for which policymakers use research Innovative best practices for engaging policymakers from those who excel at doing it and studying it Guiding questions for deciding whether to approach policymakers as an advocate or educator This book brings new ways of thinking about evidence-based policymaking- by advancing two theories, one that predicts policymakers' use of research and another that explains why research is underutilized in policymaking. This book holds the potential to advance the study of evidence-based policymaking- by proposing how policymakers use research for achieving policy ends, and also for achieving more immediate means to accomplish their long-term ends. This book also envisions a new future for evidence-based policy- by looking to the roots of what it would take to create cultural competence now and in the preparation of the next generation of researchers. This story is compelling because much of it is told in the voice of policymakers themselves by drawing on an unusual new study of state legislators. Moreover, it includes the studies and stories of two authors who have spent their university careers with one foot planted in research and the other in outreach"--
OCLC-licensed vendor bibliographic record.
Keywords: Policy sciences; FAMILY & RELATIONSHIPS / General; POLITICAL SCIENCE / Public Policy / Social Services & Welfare; SOCIAL SCIENCE / Sociology / Marriage & Family